[Damaged Fish Cannery in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a damaged fish cannery on Heimaey. The two, rectangular buildings with a broken side and top sit along a grass covered mountain to the left. Rubble, trash, and mounds of dirt and rock surround the damaged buildings throughout the photograph. More mountains are visible in the background behind a hill of black rocks. A red car sits parked on a brown path ahead. A group of people, including a child in red, walk along the path in the bottom left corner of the photograph.